3D micromechanical progressive failure simulation for fiber-reinforced composites. (1st October 2020) - Zhang, Peng; Yao, Weian; Hu, Xiaofei; Bui, Tinh Quoc
Highlights: A more practical approach for modelling microscopic progressive failure in 3D laminate is built. Modeling detailed microscopic progressive failure mechanism in 3D laminate. The failure mechanisms in composites at micro-scale are investigated from a 3D point of view. An additional phase field is introduced to regularize the material properties with sudden change. The significance of parallel computing in accelerating the modelling is demonstrated. Abstract: In this paper, the recently developed two-dimensional (2D) phase field model is further applied to study micromechanical progressive failure process in three-dimensional (3D) fiber-reinforced composites, exploring deeper insight into the intrinsic failure mechanisms caused by the sophisticated microstructures. Although more challenging, a 3D fiber-reinforced composite modelling is desired since it reveals more clearly physical progressive failure process than a 2D model. In this setting, a phase field model based modelling framework is thus adopted to capture the complicated progressive failure mechanisms in 3D composites, in particular, fiber/matrix interface debonding and kinking, matrix cracks propagation, and delamination between adjacent plies. All kinds of cracks are modelled based on cohesive zone model to obtain a more reliable prediction. This significant development of 3D analysis is a generalization of our previous 2D work, its implementation is however completely different as enhanced by parallel computing in terms of ABAQUS user-defined subroutine, which may target the real applications. Two new energy split schemes are proposed for the modelling of progressive damage in composite materials. Numerical verification and validation are given through the modelling of a unidirectional ply and of an angle ply laminate. The damage initiation, propagation, and interaction captured by the developed method are analyzed, exploring the complicated progressive failure mechanisms of fiber-reinforced composites.